Laparoscopic evaluation of pelvis in infertile women with previous genital and extra genital tuberculosis - Aggarwal, Kiran; Medha, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Genital tract tuberculosis causes infertility is a known fact but does past extra genital tuberculosis which had been treated also affects genital tract silently and causes significant genital involvement and infertility. The aim of this study was to study laparoscopic evaluation of pelvis in infertility patients with past history of treated genital and extra genital tuberculosis. Methods: 40 infertile patients with past history of treated genital (11) and extra genital (29) tuberculosis were included in the study. The study was conducted in a tertiary level hospital for one and a half years. After initial evaluation and work up and ruling out any active infection patients were posted for laparoscopic evaluation and proceed. Results: Most common site of extra genital tuberculosis was pulmonary tuberculosis in 52. 50%. Primary infertility was more common in both the groups, around 72%. Menstrual patterns were significantly different. 45.45% in women in group with genital tuberculosis presented with hypo menorrhoea as compared to only 13.79% in women with extra genital tuberculosis. Laparoscopic findings showed evidence of squealae of past tubercular infection like peritubular adhesions, omental adhesions, fibrosed distorted tubes, tubo-ovarian masses, hydrosalpinx, difficulty to visualise the tubes and ovaries and various combinations of these in most of the cases in women with genital tuberculosis (72.73%) of cases. These findings were seen in 37.93% of women with past extra genital tuberculosis. Conclusions: Genital tract may silently get invaded in primary extra genital tuberculosis. It is important for young girls affected by this to be treated diligently which might reverse the changes in time.